2015
DOI: 10.1097/gme.0000000000000311
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose paroxetine (7.5 mg) improves sleep in women with vasomotor symptoms associated with menopause

Abstract: ObjectiveSleep disturbances are common among women in midlife; prevalence increases among perimenopausal/postmenopausal women with vasomotor symptoms. Paroxetine 7.5 mg is the only nonhormonal treatment that has been approved in the United States for moderate to severe vasomotor symptoms associated with menopause. In two pivotal phase 3 studies evaluating its efficacy and safety, improvements in sleep disturbances were also prospectively evaluated.MethodsPostmenopausal women with moderate to severe vasomotor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 43 publications
(55 reference statements)
1
32
0
1
Order By: Relevance
“…Hormone therapy effectively treats hot flashes and consequently alleviates subjective sleep problems in many women (Polo-Kantola, 2011). Treatment of hot flashes with either selective serotonin or serotonin-norepinephrine reuptake inhibitors also reduces insomnia symptoms in peri- and post-menopausal women with hot flashes (Ensrud et al, 2012; Ensrud et al, 2015; Pinkerton et al, 2015). Further trials are needed to determine the effectiveness of these and other treatments in improving PSG-defined sleep in women with insomnia that develops in the context of the menopause transition.…”
Section: Discussionmentioning
confidence: 99%
“…Hormone therapy effectively treats hot flashes and consequently alleviates subjective sleep problems in many women (Polo-Kantola, 2011). Treatment of hot flashes with either selective serotonin or serotonin-norepinephrine reuptake inhibitors also reduces insomnia symptoms in peri- and post-menopausal women with hot flashes (Ensrud et al, 2012; Ensrud et al, 2015; Pinkerton et al, 2015). Further trials are needed to determine the effectiveness of these and other treatments in improving PSG-defined sleep in women with insomnia that develops in the context of the menopause transition.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies of antidepressants by menopausal women have considered sleep as an independent outcome measure. However, in a study of 600 menopausal women with moderate / severe VMS, paroxetine 7.5 mg induced a significant reduction in associated awakenings and a significant increase in total sleep time [24]. Of note, paroxetine is approved for the management of VMS by the FDA but not in Europe.…”
Section: Insomniamentioning
confidence: 99%
“…Sleep disorders are usually shared among midlife women. Studies have shown that 7.5 mg of paroxetine/day, administered for the alleviation of vascular symptoms, also reduced the number of awakenings significantly during the night and prolonged the sleeping period [38].…”
Section: The Management Of Vasomotor Disordersmentioning
confidence: 99%